Management of Kaphaja Shirshoola with special reference to Reflex Headache (International Journal of Ayurveda and Pharma Research, 2024)
Kaphaja Shirashoola, is a condition characterized by Headache in evening time accompanied by nasal blockages are symptoms commonly associated with vitiation of Kapha dosha is known as Kaphaja Shirashoola in Ayurveda. Acharya Madhavakara given the brief knowledge about the Nidana of Kaphaja Shirashoola in modern perspective it is compared to reflex headache. According to Ayurveda symptoms of Kaphaja Shirashoola are heaviness of head and dull pain and nasal congestion with headache, which tends to worsen during the Kapha kala particularly in the late afternoon and in evening. Reflex headache often arises from disturbance in other bodily systems leading to referred pain in the cranial region. In this case According to the classics Nasya with Anutaila and Shamanayoga along with proper Pathya Ahara and Vihara. All the symptoms were relieved and subject feel lightness of the body.